Y is the answer for four right angles
Answer: 7 1/2
Step-by-step explanation:
Answer:
Exact Form:
c = −
1
2
Decimal Form:
c = −
0.5
Step-by-step explanation:
Answer: x^2 -10x + 24
Step-by-step explanation:
(x-6) (x-4)
= x^2 - 6x - 4x + 24
= x^2 -10x + 24
Answer: Substitution
Step-by-step explanation:
GIVEN:
y=3x
2x+4y=12
Then, 2x+4(3x)=12
-----------------------------------------
Substitution: replacing one variable in terms of another variable.
As we can see from the given aspects, y=3x, and the conclusion expression has no y instead of 3x. This means it represented y in terms of x, which fits the definition of substitution that replaces one variable.
Hope this helps!! :)